Cohort comparisons: emotional well-being among adolescents and older adults - Momtaz YA (Dove Medical Press, 2014)
Yadollah Abolfathi Momtaz,1 Tengku Aizan Hamid,1,2 Rahimah Ibrahim1,21Institute of Gerontology, 2Department of Human Development and Family Studies, Faculty of Human Ecology, Universiti Putra Malaysia, Serdang, Selangor, MalaysiaBackground: There are several negative stereotypes about older adults that have negatively influenced people's attitude about aging. The present study compared emotional well-being between older adults and adolescents.Methods: Data for this study came from 1,403 community-dwelling elderly persons and 1,190 secondary school students and were obtained from two national cross-sectional surveys. Emotional well-being was measured using the World Health Organization-Five Well-Being Index. Data analysis was conducted using a multivariate analysis of covariance with SPSS software version 20 (IBM Corporation, Armonk, NY, USA).Results: Elderly people significantly scored higher levels of emotional well-being (mean, 62.3; standard deviation, 22.55) than younger people (mean, 57.9; standard deviation, 18.46; t, 5.32; P≤0.001). The findings from the multivariate analysis of covariance revealed a significant difference between older adults and younger people in emotional well-being [F(3, 2587)=120.21; P≤0.001; η2=0.122] after controlling for sex.Conclusion: Contrary to negative stereotypes about aging, our findings show a higher level of emotional well-being among older adults compared with younger people.Keywords: aged, ageism, emotional well-being, positive aging